Low temperature exposure induces browning of bone marrow stem cell derived adipocytes in vitro - Velickovic, Ksenija; Lugo-Leija, Hilda Anaid; Bloor, Ian; Law, James; Sacks, Harold; Symonds, Michael E.; Sottile, Virginie (Nature Publishing Group, 2018)
Brown and beige adipocytes are characterised as expressing the unique mitochondrial uncoupling protein (UCP)1 for which the primary stimulus in vivo is cold exposure. The extent to which cold-induced UCP1 activation can also be achieved in vitro, and therefore perform a comparable cellular function, is unknown. We report an in vitro model to induce adipocyte browning using bone marrow (BM) derived mesenchymal stem cells (MSC), which relies on differentiation at 32°C instead of 37°C. The low temperature promoted browning in adipogenic cultures, with increased adipocyte differentiation and upregulation of adipogenic and thermogenic factors, especially UCP1. Cells exhibited enhanced uncoupled respiration and metabolic adaptation. Cold-exposed differentiated cells showed a marked translocation of leptin to adipocyte nuclei, suggesting a previously unknown role for leptin in the browning process. These results indicate that BM-MSC can be driven to forming beige-like adipocytes in vitro by exposure to a reduced temperature. This in vitro model will provide a powerful tool to elucidate the precise role of leptin and related hormones in hitherto functions in the browning process.